IGF and nutrition in health and disease - Houston, M. Sue; Holly, Jeffrey M. P.; Feldman, Eva L. (Nutrition and health, 2005)
Overview and molecular aspects of the insulin-like growth factor system / Martin L. Adamo ... [et al.] -- Regulation of IGF-I by nutrition / Jean-Paul Thissen ... [et al.] -- Nutrition and IGF proteins in chronic malnutrition and critical illness / Pei-Ra Ling and Bruce R. Bistrian -- The insulin-like growth factors and assessment of nutritional status / M. Sue Houston -- Regulation of growth and the insulin growth factor system by zinc / Ruth S. MacDonald -- The role of the insulin-like growth factor system in pre- and postnatal growth, development, and tumorigenesis / Charles T. Roberts, Jr. --